CARBON ABSORPTION ABILITY OF PINE FOREST PLANTATIONS IN CHERNIHIV POLISSIA - Moroz, V. V.; Nykytiuk, Y. A. (Scientific Progress & Innovations, 2020)
According to the signed Paris Climate Agreement, Ukraine is faced with the task to prevent the global average air temperature from rising above 2.5 °C in order to avoid an increase in droughts, extinction of certain species of plants and animals, drying up and diseases of tree species, etc. To preserve and increase the number of natural carbon absorbents, scientists pay particular attention to the system of improving the management of forest, soil, and other natural resources. Among thirty main forest-forming species in Ukraine, Scots pine (Pinus silvestris L.) is the predominant tree species, in Chernihiv Polissia, in particular, the area under it is 214.2 thousand hectares, which makes 61 % of all tree plantations. To establish the car- bon absorption capacity of pine plantations in Chernihiv Polissia we have laid temporary test areas (TTAs) at the following state-owned enterprises: Horodnianske Forestry, Dobrianske Forestry, Koriukivske Forest- ry, and Nizhynske Forestry. Applying the methods of P. I. Lakyda, A. A. Storochynsky, O. I. Poluboiarynov, A. S. Atkin, A. I. Kobzar, we established a phyto-mass of pine plantations in a completely dry state and obtained conversion coefficients that made it possible to estimate the difference between CO2 emissions and carbon absorption. According to the conducted analysis of distributing forest areas under pine plantations in Chernihiv Polissia, the overwhelming majority is occupied by pine forests of the IVth category (operational), their share is 64 %, and that is why their carbon absorption capacity is higher. Climatic changes during 1968–2018 were analyzed, and the tendency of increasing the average annual air temperature by 2.5 оС in the studied regions was established. It has been found that the pine forests of Chernihiv Polissia annually absorb 34.0 thousand tons of carbon from the air, which is approximately 1.37–2.15 % of the annual carbon emissions into the atmospheric air, which in turn has a positive impact on the environmental state in the region of studies.